Costco wholesale: the global expansion dilemma. Issue 1 (21st March 2022) - Kumar, Abhishek; Kar, Sanjay Kumar; Mishra, Saroj Kumar; Bansal, Rohit; Harichandan, Sidhartha
Abstract : Learning outcomes: This case will enable students to understand the operations and business model of an international retailer. The case offers enough insights and learning on a retailer who enters a different market and collaborates with the local players to gain market access; and to understand the marketing techniques and strategies of an international retailer to capitalise on market opportunities. Case overview/synopsis: The case is about a third largest US-based multinational Costco Wholesale corporation which is a giant retailer. The company operated at 803 locations with a revenue of $166.7bn, which makes it the third largest global retailer in 2020. The case offers comprehensive insight into Costco Wholesale's business model, distribution strategy, marketing techniques and internationalisation. The authors further discuss that how Costco put forth its model among different range of customers and provided them with high-quality products at a comparatively lower price. The focus of the case is towards the Asian expansion of Costco. In subsequent parts, the strategies and challenges of Costco with respect to its Asian competitors have also been discussed. After generating experience in Asian markets, Costco has considered China as its next destination. The case also discusses the foreign retailers' success, failure and retail format. Complexity academic level: This case is designed for undergraduate and postgraduate classes of management and business administration. Supplementary materials: Teaching notes are available for educators only. Subject code: CSS 8: Marketing.